Oxford American children's encyclopedia. Volume 8, biography. (New York : Oxford University Press, 1998)
Presents alphabetically arranged biographies of prominent individuals.
3-6
Keywords: Biography -- Dictionaries; Children's encyclopedias and dictionaries; Biography -- Dictionaries; Encyclopedias and dictionaries; Biography -- Dictionaries; Encyclopedias and dictionaries